Grenoble entre natures et cultures : exemple de la valorisation de l’agriculture périurbaine grenobloise - Anthony Tchékémian (Projets de Paysage)
In Grenoble, the mountains have an influence on the demands, expectations and practices of urban nature. In addition, the outdoor activities, reflect a growing willingness to do recreational activites in the mountains and the countryside on the outskirts of the city. Basically, these activities are an opportunity to create a relationship to nature. The institutions for town planning and the development of the recreation areas of Grenoble try to meet the demands and expectations of urban natures, maintaining and developing peri-urban agriculture. Meeting the urban demands and expectations in terms of products and landscapes is the new challenge of the peri-urban agriculture. Taking into account the social demand for nature, as a pattern of the operating systems, allows to further develop the debate around agriculture, through the role assigned to peri-urban agriculture. Thus, agriculture claims to be multifunctional, with a new suburban culture and a return to nature that are not necessarily a return to “a job on the fields”. Agriculture must not only ensure the quality of its products, territories and rural landscapes as a production unit, but also as a place for recreational activities and identity.